The Distributed Virtual Network for High Fidelity, Large Scale Peer to Peer Network Simulation - Foo Kune, Denis; Malchow, Tyson; Tyra, James; Hopper, Nicholas J.; Kim, Yongdae (My University, 2010)
The ability to analyze the behavior of large distributed systems can be limited by the modeling tools used. The Distributed Virtual Network (DVN) is a discrete event network simulator providing a platform for realistic, high fidelity, scalable and repeatable simulations of large distributed systems. With a global view of the network, it provides the ability to quantify the behavior of the system under stress and attack conditions. We present the architecture of the simulator along with the simulation results from a real world P2P protocol implementation ported to DVN. We also compare DVN with another similar tool, outlining the benefits of our contribution.